2017
DOI: 10.1021/acs.orglett.7b01625
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Heterogeneous Chiral Titanium Catalyst Derived from Silica-Supported 3-Aryl H8-BINOL to Enantioselective Alkylation and Arylation of Aldehydes

Abstract: A 3-aryl H-BINOL was grafted on the surface of silica gel using a hydrosilane derivative as a precursor, and the resulting silica-supported ligand (6 mol %) was employed in the enantioselective alkylation and arylation of aldehydes in the presence of Ti(OPr). The reactions using EtZn, EtB, and aryl Grignard reagents all afforded the corresponding adducts in high enantioselectivities and yields. The silica-immobilized titanium catalyst could be reused up to 14 times without appreciable deterioration of the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…47, the ethylation of 4-chlorobenzaldehyde using Et 2 Zn was studied for 10 runs with only a small reduction in yield (from 91 to 85%) and enantioselectivity (from 96 to 90%), while the arylation of 1-naphthaldehyde with PhMgBr was reported to occur with 85% yield (94% ee) in the first run and 99% yield (88% ee) for the tenth, although some variability of results within this range of values was obtained for this process for the whole series of experiments. 274 The ethylation of 1-naphthaldehyde with Et 3 B showed excellent reproducibility in terms of yield and enantioselectivity for ten consecutive runs (85-89% yield and 96% ee).…”
Section: Number Of Runsmentioning
confidence: 89%
See 1 more Smart Citation
“…47, the ethylation of 4-chlorobenzaldehyde using Et 2 Zn was studied for 10 runs with only a small reduction in yield (from 91 to 85%) and enantioselectivity (from 96 to 90%), while the arylation of 1-naphthaldehyde with PhMgBr was reported to occur with 85% yield (94% ee) in the first run and 99% yield (88% ee) for the tenth, although some variability of results within this range of values was obtained for this process for the whole series of experiments. 274 The ethylation of 1-naphthaldehyde with Et 3 B showed excellent reproducibility in terms of yield and enantioselectivity for ten consecutive runs (85-89% yield and 96% ee).…”
Section: Number Of Runsmentioning
confidence: 89%
“…47, the regeneration of the Ti-catalyst used for 10 successive runs for the ethylation of 1-naphthaldehyde with Et 3 B was studied revealing that the regenerated catalyst achieved the same performance for four additional cycles. 274 Lunden et al reported that the polymer-supported pyridinebis(oxazoline) ligand developed for the ytterbium-catalyzed silylcyanation of benzaldehyde could be recovered from the reaction mixture and regenerated for at least 30 times. 264 In their study of silica-supported organocatalysts for stereoselective Diels-Alder reactions under flow conditions, Porta et al analysed the regeneration of the organocatalytic column after 200 h of use and found that in this way the life of the reaction was prolonged to 300 h in total, but the performance of this regenerated catalytic column was slightly lower than that of the fresh system.…”
Section: Regeneration and Reusementioning
confidence: 99%
“…For example, they are used as chiral ligands, chiral phase transfer catalysts, etc. The most representative compound including 1,1′‐binaphthalene‐2,2′‐diol (referred to as 2,2′‐BINOL), 1,1′‐binaphthalene‐8,8′‐diol (referred to as 8,8′‐BINOL), and 1,1′‐ Binaphthalene‐2,2′‐diamine (referred to as BINAM), which have been studied theoretically by some relevant scholars. In recent years, it has been found the two‐dentate ligand without C 2 symmetry factors, such as 2‐amino‐2′‐hydroxy‐1,1′‐binaphthyl (denoted as NOBIN hereafter), is also an excellent chiral ligand .…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, we decided to associate (R)-and (S)-binol to increase the chiral environment. 26,27 Therefore, such association could be appropriate when comparing the results obtained in this work, since the use of the co-catalyst D demonstrated the most promising results. These results are probably due to the action of D as a Lewis acid, interacting with the nitro group in a more expressive way when compared to other co-catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of Lewis acids in this organocatalysis was also investigated, since they have shown promising results. 26 In this context, the use of Ti(O i Pr) 4 (D) and BF 3 .EtO 2 (H) were evaluated under different conditions ( Table 2, entries 21-29 and 33).…”
Section: Resultsmentioning
confidence: 99%